Seed biopriming with Trichoderma strains isolated from tree bark improves plant growth, antioxidative defense system in rice and enhance straw degradation capacity - Swain, Harekrushna; Adak, Totan; Mukherjee, Arup K.; Sarangi, Sarmistha; Samal, Pankajini; Khandual, Ansuman; Jena, Rupalin; Bhattacharyya, Pratap; Naik, Soumendra K.; Mehetre, Sayaji T.; Baite, Mathew S.; Kumar M, Sunil; et al. (Frontiers Media, 2021)
This study is a unique report of the utilization of Trichoderma strains collected from even tree barks for rice plant growth, its health management, and paddy straw degradation. Seven different spp. of Trichoderma were characterized according to morphological and molecular tools. Two of the isolated strains, namely Trichoderma hebeiensis and Trichoderma erinaceum, outperformed the other strains. Both of the strains controlled four important rice pathogens, i.e., Rhizoctonia solani (100%), Sclerotium oryzae (84.17%), Sclerotium rolfsii (66.67%), and Sclerotium delphinii (76.25%). Seed bio-priming with respective Trichoderma strains reduced the mean germination time, enhanced the seedling vigor and total chlorophyll content which could be related to the higher yield observed in two rice varieties; Annapurna and Satabdi. All the seven strains accelerated the decomposition of rice straw by producing higher straw degrading enzymes like total cellulase (0.97–2.59 IU/mL), endoglucanase (0.53–0.75 IU/mL), xylanase (145.35–201.35 nkat/mL), and laccase (2.48–12.60 IU/mL). They also produced higher quantities of indole acetic acid (19.19–46.28 μg/mL), soluble phosphate (297.49–435.42 μg/mL), and prussic acid (0.01–0.37 μg/mL) which are responsible for plant growth promotion and the inhibition of rice pathogen populations. Higher expression of defense enzymes like catalase (≥250% both in shoot and root), peroxidase (≥150% in root and ≥100% in shoot), superoxide dismutase (≥ 150% in root and ≥100% in shoot), polyphenol oxidase (≥160% in shoot and ≥120% in shoot), and total phenolics (≥200% in root and ≥250% in shoot) as compared to the control indicates stress tolerance ability to rice crop. The expression of the aforementioned enzymes were confirmed by the expression of corresponding defense genes like PAL (andgt;3-fold), DEFENSIN (andgt;1-fold), POX (andgt;1.5-fold), LOX (andgt;1-fold), and PR-3 (andgt;2-fold) as compared to the non-treated control plants. This investigation demonstrates that Trichoderma strains obtained from tree bark could be considered to be utilized for the sustainable health management of rice crop.